The Correlation of Transaminase Enzymes on the Prognosis of Covid-19 Patients in the ICU Infection Center Dr. Wahidin Sudirohusodo General Hospital Makassar - Dominiques Reggy Marfilan; Hisbullah; A. M. Takdir Musba; Syamsul Hilal Salam; Faisal Muchtar; Haizah Nurdin (Britain International of Exact Sciences (BIoEx) Journal, 2021)
Corona Virus Disease 2019 (COVID-19) is an infectious disease that has been designated as a worldwide pandemic. Symptoms of Covid-19 are not only respiratory symptoms but also extrapulmonary symptoms, including the discovery of impaired liver function in the form of increased transaminase enzymes. Therefore, this study was conducted to see the correlation of transaminase enzymes with the prognosis of COVID-19 patients treated in the Intensive Care Unit (ICU) Dr. Wahidin Sudirohusodo Hospital. The study was conducted on June to August 2021. The cross-sectional analytical research method used retrospective medical record data for the period from July to December 2020 with a sample of 137 patients with COVID-19 confirmed. From the results of the Pearson test, patients with increased SGOT were associated with a mortality prognosis (p=0.000, p<0.05) with a correlation coefficient (r) of -0.383 and an increase in SGPT were associated with a mortality prognosis (p=0.013, p<0.05) with a correlation coefficient (r) of -0.211. From the results of the Kruskal Wallis test, there were differences in prognosis in patients with increased SGOT and SGPT grades 1,2,3, and 4 (p = 0.000 and p = 0.028). There is a correlation between the increased transaminase enzymes with the prognosis of the patient's mortality. Patients with severe elevated SGOT and SGPT enzymes had a greater prognosis of mortality than those with mild enzyme elevations. Extrapulmonary symptoms of stroke were associated with increased SGOT and myocardial infarction symptoms, and nephropathy was associated with increased SGOT and SGPT. Comorbid coronary artery disease and hepatitis were associated with increased SGOT and SGPT.